2016
DOI: 10.5194/amt-9-1341-2016
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an enclosed gas analyzer sampling system for measuring eddy covariance fluxes of H<sub>2</sub>O and CO<sub>2</sub>

Abstract: Abstract. Several initiatives are currently emerging to observe the exchange of energy and matter between the earth's surface and atmosphere standardized over larger space and time domains. For example, the National Ecological Observatory Network (NEON) and the Integrated Carbon Observing System (ICOS) are set to provide the ability of unbiased ecological inference across ecoclimatic zones and decades by deploying highly scalable and robust instruments and data processing. In the construction of these observat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…Generally it is thought that the theoretical approach easily underestimates the high-frequency spectral attenuation for closed-path systems, because of potential variations in the mass flow rates and relative uncertainty in the flow regime (Aubinet et al, 2000). Recent studies, both in the lab and in the field, have also demonstrated the important effects that different dust filters and rain caps (typically mounted at the tube inlet) have on the EC system cut-off frequency (Aubinet et al, 2016;Metzger et al, 2016). Such effects are not included in the theoretical approach.…”
Section: Critical Steps and Recommendations For Closed-path Systemsmentioning
confidence: 99%
“…Generally it is thought that the theoretical approach easily underestimates the high-frequency spectral attenuation for closed-path systems, because of potential variations in the mass flow rates and relative uncertainty in the flow regime (Aubinet et al, 2000). Recent studies, both in the lab and in the field, have also demonstrated the important effects that different dust filters and rain caps (typically mounted at the tube inlet) have on the EC system cut-off frequency (Aubinet et al, 2016;Metzger et al, 2016). Such effects are not included in the theoretical approach.…”
Section: Critical Steps and Recommendations For Closed-path Systemsmentioning
confidence: 99%
“…GitHub provides distributed version control and has become widely used by scientific research groups because it is free, open-source, and provides several features that make it useful for managing artifacts of scientific research (Ram, 2013). Git allows multiple users and developers to simultaneously access and collaborate on a remote repository by means of independent "forks" or replicas of the entire repository (Paarsch and Golyaev, 2016). Figure 3 shows NEON's Git workflow: at any given time (1) the official, stable eddy4R source code resides on NEON's GitHub repository.…”
Section: Git Distributed Version Control (Devops Verify Andmentioning
confidence: 99%
“…In Lee et al, 2015;Metzger et al, , 2013Metzger et al, , 2016Salmon et al, 2015;Serafimovich et al, 2013;Starkenburg et al, 2016;Vaughan et al, 2016;Xu et al, 2017). eddy4R currently consists of four packages: eddy4R.base, eddy4R.qaqc, eddy4R.turb, and eddy4R.erf.…”
Section: The Development and Operations (Devops) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…They have a longer measurement chamber of 12.5 cm compared to the few mm of the Lyman-Alpha. The LICOR sensors in different forms are used at automated field stations for research networks covering large temporal and spatial scales, and they are therefore well characterised concerning the transfer function of different components (Metzger et al, 2016). The closed-path sensors requiring a gas sampling system can be affected by high-frequency attenuation, so inlets and tubes have to 30 be dimensioned reasonably (Aubinet et al, 2016;Metzger et al, 2016).…”
mentioning
confidence: 99%